EFFORT COUNTERMEASURES WITH ACTION CRIMINAL COLLECTIVE THEFT SAME IN MODE BREAKING THE CAR GLASS - Karina, Ica; Siahaan, Ade Juliany; Fitriani, Fitriani (NOMOI Law Review, 2023)
The discomfort that arises in the public is not without reason, due to the intensity of the crime following which the numbers are very high. Cases of theft using car glass finishing mode often occur in the city of Medan due to several problems. The problem is that the background of the perpetrator of the crime of theft is seen from economic factors or dependence on illegal drugs such as narcotics and other social factors. The research method used is a normative juridical legal research method. The approach used is the statutory approach, the tracing system used is the library research method The research results show that the modus operandi of the perpetrators of the crime criminal theft Which done in a way together with mode breaking a car window is by breaking the keyhole, breaking glass, making fake keys, or in other neater ways. Already It is an obligation for police officers to learn new methods which was carried out by the perpetrator of the theft by breaking the car window so that can finish disclosure case or even Possible can anticipate something follow criminal crime in the future.